COMPARISON OF DIFFERENT TREATMENT METHODS FOR LOCALIZED AND GENERALIZED SIMPLE DENTURE STOMATITIS - KADİR, TANJU; ÖZKAN, YASEMİN (BLACKWELL SCIENCE LTD, 1995)
The purpose of this study was to compare the treatment effects of fluconazole, fluconazole plus chlorhexidine and the fitting of new dentures upon the treatment of denture stomatitis and 15 subjects with clinical evidence of localized simple denture stomatitis were investigated clinically and mycologically. Patients with clinical evidence of generalized simple denture stomatitis were divided into three treatment groups. The first group was given 50 mg of fluconazole tablets daily for 2 weeks. The second group were instructed to apply chlorhexidine solution to the inner surface of the denture twice a day in addition to fluconazole treatment for 2 weeks. New dentures were constructed for the third group. Patients with clinical evidence of localized simple denture stomatitis were fitted new dentures without antifungal therapy. Palatal swabs were taken from each subject before, immediately after, and 2 weeks after the end of treatment, and the samples were examined mycologically in order to identify yeast colonies. It was found that for generalized simple denture stomatitis, treatment with fluconazole plus chlorhexidine resulted in better improvement of palatal inflammation than that by either fluconazole or the fitting of new dentures without medication, Whereas fitting new dentures did not reduce inflammation in patients with generalized simple denture stomatitis, the beneficial effects of prosthetic treatment were seen in patients with localized simple denture stomatitis.
Keywords: EFFICACY